1993
DOI: 10.1177/019459989310900411
|View full text |Cite
|
Sign up to set email alerts
|

The role of gentle ventilation in prevention of subglottic stenosis in the newborn

Abstract: Prolonged endotracheal intubation has become the standard of care in most neonatal units for maintenance of mechanical ventilation in the presence of respiratory distress. Unfortunately this approach has become associated with significant complications, including acquired subglottic stenosis. We have successfully used nasal continuous positive airway pressure to avoid or decrease the incidence and duration of endotracheal intubation. With use of this technique we have been able to significantly reduce sequelae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Our incidence of 27/1847 (1.5%) in infants with a birth weight of <1500 g is comparable with Suzumura et al 16 and Nicklaus et al 9 who reported incidences of 3.1% and 2.4% respectively. Gaynor and Danoff15 reported an incidence of 0% in infants <1500 g, although they only had a denominator of 128 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our incidence of 27/1847 (1.5%) in infants with a birth weight of <1500 g is comparable with Suzumura et al 16 and Nicklaus et al 9 who reported incidences of 3.1% and 2.4% respectively. Gaynor and Danoff15 reported an incidence of 0% in infants <1500 g, although they only had a denominator of 128 patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Nonetheless, prolonged intubation and traumatic intubation, even in neonates, carries a morbidity and an overall rate of symptomatic subglottic stenosis of 0.2%. 10,11 This report did not attempt to determine if the rate of subglottic stenosis changed during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in adults and older children, benefits have been claimed for the use of high-volume low-pressure cuffs, as well as frequent cuff pressure monitoring and soft cuffs at the larynx. 3,5,6 The size of the endotracheal tube relative to the airway lumen has been examined, and recommendations have been made to avoid an excessively tight fit in the subglottis. 7,8 In an effort to minimize friction trauma by tube motion, nasotracheal intubation has been supported and tube fixation devices have also been devised.…”
mentioning
confidence: 99%